Bier’s block: A Case Report - Kharbuja, Kalpana; Sharma, Mahesh; Sharma, Nil Raj (Journal of Lumbini Medical College, 2016)
Introduction: Intravenous Regional Anesthesia (IVRA) has been first described in 1908 by the German surgeon August KG Bier. Although the technique was convenient to perform and effective in giving surgical anesthesia, the recent plexus block techniques have largely replaced the “Bier’s block” instantly because of time limitations and safety considerations of IVRA. Throughout the years, modifications in procedure and new pharmacologic adjuvants have shown to prevent toxic reactions to anesthetics and mitigate limitations of IVRA, still IVRA can be preferred as choice of anesthesia for short procedures. Case Report: We present a case of 86 yr old male who was operated for radius fracture after a fall injury under Bier’s Block or IVRA technique. Conclusion: IVRA can be the choice of anesthesia for short procedures because of rapid onset of anesthesia, easy administration and cheaper cost with special considerations on its side effects, complications which can be the outcome of technical errors. DOI: https://doi.org/10.22502/jlmc.v3i1.65